The Effect of Inflation on Economic Growth in Tanzania - Sanga, Goodluck John; Kongolo, Mukole; Mnongya, Rosemary (Contemporary Research: An Interdisciplinary Academic Journal, 2023)
The research examines the effect of inflation on economic growth in Tanzania. The study employs the secondary time series data from 1970 to 2020 taken from the Bank of Tanzania, and the VECM is used to find the cointegration between variables to show the short-run and long-run dynamics. Graphical analysis and Augmented Dickey-Fuller tests are conducted to find the unit root in the model. All variables are stationary and integrated in the same order I (1). The results show that the error correction is significantly negative. That is, the annual rate of adjustment required to achieve long-run equilibrium is 28.31 percent. Based on the findings in the short-run, the extended money supply and interest rates have negative and insignificant effects on GDP, while the exchange rate has an inversely significant effect on GDP. Inflation targeting has a favourable insignificant effect on GDP. Long-run results show that extended money supply, exchange rates, and interest rates have positive significant effects on economic growth, whereas inflation targeting has negative significant effects on GDP. It is recommended that the government, policymakers, and financial institutions focus on managing inflation by the prudent implementation of fiscal and monetary policies and maintaining a regulation of interest rates, the extended money supply, and real exchange rates also inflation targeting should be emphasised by improving the central bank's communication, transparency, and accountability to avoid inflation volatility and stimulate economic growth.